2015
DOI: 10.5830/cvja-2015-027
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mid-term outcome after cryo-balloon ablation of atrial fibrillation using post-procedure high-sensitivity troponin level

Abstract: ObjectiveHigh-sensitivity troponin I (hsTnI) assays lead to, among other things, improvement in the detection of myocardial injury and improved risk stratification of patients with atrial fibrillation (AF). The aim of this study was to investigate the association between post-procedure cardiac biomarkers and clinical outcome in patients undergoing cryo-balloon ablation (CA) for AF.MethodsA total of 57 patients (mean age 55.1 ± 12.2 years, 50.9% female) with symptomatic paroxysmal AF underwent the CA procedure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…This study included 25 patients using RFA and 50 patients with CBA and a small number of cases might be obtained different results. Another report demonstrated that a lower postablation hs‐TnI level may predict an increased AF recurrence rate 20 . In this study, 57 patients using CBA were included and LRAF patients showed lower hs‐TnI level.…”
Section: Discussionmentioning
confidence: 77%
“…This study included 25 patients using RFA and 50 patients with CBA and a small number of cases might be obtained different results. Another report demonstrated that a lower postablation hs‐TnI level may predict an increased AF recurrence rate 20 . In this study, 57 patients using CBA were included and LRAF patients showed lower hs‐TnI level.…”
Section: Discussionmentioning
confidence: 77%
“…[1921] Among them, MR was demonstrated to have a detrimental impact on AF ablation outcomes. [5] Moreover, the grade of MR severity had positive correlation with the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cardiac troponins have been associated with new-onset AF in patients admitted to hospital with acute ischaemic stroke [24] and also with incident AF in community-based cohorts [1,2,3]. On the other hand, the evidence of any predictive abilities of cardiac troponins in rhythm outcome after electrical cardioversion is scarce, and the results regarding ablation outcome are conflicting [25,26]. Considering that no survival advantage has been shown from a rhythm control strategy in AF [27], one should perhaps not expect predictors of recurrence and mortality in AF to overlap.…”
Section: Discussionmentioning
confidence: 99%